Pro Android 5 - MacLean, Dave; Komatineni, Satya; Allen, Grant (Apress, 2015)
Pro Android 5 shows you how to build real-world and fun mobile apps using the Android 5 SDK. This book updates the best-selling Pro Android and covers everything from the fundamentals of building apps for smartphones, tablets, and embedded devices to advanced concepts such as custom components, multi-tasking, sensors/augmented reality, better accessories support and much more. Using the tutorials and expert advice, you'll quickly be able to build cool mobile apps and run them on dozens of Android-based smartphones. You'll explore and use the Android APIs, including those for media and sensors.